The Role of Photodynamic Therapy in Triggering Cell Death and Facilitating Antitumor Immunology - Tan, Liuchang; Shen, Xiaoxiao; He, Zhiqiang; Lu, Yuangang (Frontiers in Oncology, 2022)
Cancer is a major threat to human health because of its high mortality, easy recurrence, strong invasion and metastasis. Photodynamic therapy (PDT) is one of the most promising therapeutic methods for tumor treatment. Compared with traditional treatment methods, PDT is less invasive and does not easily damage normal tissues. Most of the effects of this treatment are due to the direct effects of singlet oxygen and reactive oxygen species. PDT can provide a source of active oxygen for Fenton reaction, which enhance the induction of ferroptosis and improve the efficacy of PDT in antitumor therapy. Additionally, in contrast to chemotherapy and radiotherapy, PDT offers a remarkable advantage of stimulating an immune response, which can effectively induce immunogenic cell death (ICD) and stimulate immunity. PDT is an ideal minimally invasive treatment method for tumors. In this paper, according to the characteristics of anti-tumor immunity of PDT, some tumor treatment strategies of PDT combined with anti-tumor immunotherapy are reviewed.